2006
DOI: 10.1530/rep.1.01217
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cell nuclear transfer alters peri-implantation trophoblast differentiation in bovine embryos

Abstract: Abnormal placental development limits success in ruminant pregnancies derived from somatic cell nuclear transfer (SCNT), due to reduction in placentome number and consequently, maternal/fetal exchange. In the primary stages of an epithelial-chorial association, the maternal/fetal interface is characterized by progressive endometrial invasion by specialized trophoblast binucleate/giant cells (TGC). We hypothesized that dysfunctional placentation in SCNT pregnancies results from aberration in expression of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 52 publications
5
45
0
4
Order By: Relevance
“…1). The overall recovery was 11/18 (61.1%) which compares favourably to data reported by others [27,28] thus confirming the developmental potential of the adult cell line derived from Wagyu cattle used in our experiments.…”
Section: Resultssupporting
confidence: 91%
“…1). The overall recovery was 11/18 (61.1%) which compares favourably to data reported by others [27,28] thus confirming the developmental potential of the adult cell line derived from Wagyu cattle used in our experiments.…”
Section: Resultssupporting
confidence: 91%
“…1, 2) were associated with relative immaturity of vessels of the placental villi, as determined by reduced or no immunohistochemical expression of von Willebrand factor and calponin (Figs. [3][4][5][6], 79 a marker of late differentiation in vascular smooth muscle cells. 56 Placental vasculogenesis was significantly reduced as indicated by lack of CD34 expression by individual foetal blood vessels, 79 similar to the abnormal placental vasculogenesis observed with spontaneous abortions in humans.…”
Section: Morphologic Pathology Of Scnt Placentaementioning
confidence: 99%
“…19 Thus, although the 2 gene products exert somewhat opposing effects, their simultaneous overexpression leads to failure to stimulate binucleate cell differentiation by trophoblastic cells and reduced binucleate cell numbers. 3 In placentae of nonviable bovine SCNT embryos at 60 days of gestation, cDNA macroarray analysis revealed a twofold increased expression of IGF2, 75 overexpression of which in transgenic mice is embryonic lethal, 98 and less than 50% reduction of hemoglobin alpha 1, hemoglobin alpha 2, and the bovine homologues of spectrin, beta, erythrocytic and spectrin, beta, nonerythrocytic 1. 75 Genetic studies of the underlying mechanisms of placental defects in SCNT sheep have not been as extensive as those in cattle or mice because of the limited knowledge of sheep genetics.…”
Section: Pathogenesismentioning
confidence: 99%
“…Although, the morphologic appearance of SCNT embryos does not differ from that of in vitro fertilized embryos, the potential to develop to term dramatically differs between SCNT and IVF embryos (Li et al 2005(Li et al , 2006a(Li et al , b, 2008Kato et al 2007). Research using SCNT technology suggested that abnormal expression of genes during the earliest stages of development could be the reason of embryonic losses (Arnold et al 2006). Abnormal gene expression might be accountable for the observed phenotypes in embryos produced by SCNT, not only during early embryonic development, but also during gestation and parturition leading in many cases to the so called abnormal offspring syndrome (AOS; Garry et al 1996;Ranilla et al 1998;Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 99%